Comparative Analysis of Korean Animalistic Fairy Tales - Madinabonu, Yusufjonova (Miasto Przyszłości, 2023)
The article is devoted to the analysis of animalistic symbols and images in Korean fairy tales. The object of the study was Korean folk tales. Based on the analysis were identified - peak and symbolic images in researched us fairy tales.